Digital Business Contracts from the Perspective of Indonesian Civil Law - Rr. Lyia Aina Prihadiati; Sendi Sanjaya (Jurnal Ilmu Hukum Kyadiren, 2026)
The rapid expansion of the digital economy in Indonesia has led to increased use of digital business contracts, while simultaneously raising legal issues concerning legal certainty, the validity of electronic contracts, and personal data protection. This study analyzes drafting techniques for digital business contracts that are consistent with Indonesian civil law principles, examines the regulatory influence of the Electronic Information and Transactions Law (Law No. 11 of 2008 as amended by Law No. 1 of 2024) and Government Regulation No. 71 of 2019, and explores the implications of Law No. 27 of 2022 on Personal Data Protection for the formulation of contractual clauses in digital environments. This research employs a normative juridical method using statutory, conceptual, and comparative approaches based on a literature review. The findings indicate that effective digital contracts must integrate the principles of freedom of contract, good faith, consensualism, and legal certainty through explicit electronic consent, certified electronic signatures, and transparent data protection provisions. Accordingly, the harmonization of contract law, electronic transaction regulations, and personal data protection law constitutes a fundamental requirement for establishing a secure and reliable digital business ecosystem in Indonesia.